Landmark Cases of Civil Liability: A Comparative Analysis of Peruvian and Italian Case Law - Tapia Cornejo, Bruno Alonso Samuel (2025)
This research compared the roles of civil liability in the judicial doctrines of Peru and Italy through a detailed examination of relevant rulings and scholarship. Frequent trends were identified, and emphasis was placed on landmark cases. The findings revealed that Peruvian case law focuses on the compensatory function, unlike the Italian approach, which broadens its perspective toward preventive, social, and punitive roles. Although both nations agree on the protection of the injured party, they differ in the allocation of liability. The study concludes that comparative judicial dogmatics show diverse perspectives on the role of civil liability and raise questions about the importance of adopting a broader perspective in the Peruvian context that includes aspects of prevention and social protection.